Evaluation of Habenaria aitchisonii Reichb. for antioxidant, anti-inflammatory, and antinociceptive effects with in vivo and in silico approaches - Asiri, Saeed Ahmed; Shabnam, Madeeha; Zafar, Rehman; Alshehri, Osama M.; Alshehri, Mohammed Ali; Sadiq, Abdul; Mahnashi, Mater H.; Jan, Muhammad Saeed (Frontiers in Chemistry, 2024)
Habenaria aitchisonii Reichb was analyzed in this research including its chemical composition, in vitro antioxidant, anti-inflammatory, acute oral toxicity, and antinociceptive activity. Chloroform and ethyl acetate fraction were proven to be the most powerful fraction based on in vitro antioxidant, antiinflammatory, and analgesic activities. The acute oral toxicity of the crude methanolic extract was deliberated prior to in vivo studies. The acetic acid and formalin tests were used to measure the antinociceptive effect and the potential mechanisms involved in antinociception were explored. The carrageenan-induced paw edema was used to examine the immediate anti-inflammatory effect, and many phlogistic agents were used to determine the specific mechanism. Furthermore, for ex-vivo activities the mice were scarified, forebrain was isolated and antioxidant level of glutathione (GSH), superoxide dismutase (SOD), TBARS and catalase (CAT) were estimated using UV spectrophotometer. At oral dosages up to 3000 mg/kg, no toxicity was seen. When compared to the standard drug, the antinociceptive impact was much higher. Both the inflammatory and neurogenic phases of that of the formalin experiment revealed analgesic effect in chloroform and ethyl acetate fractions. In carrageenan anti-inflammatory assay the chloroform fraction (Ha.Chf) was the most potent fraction. We further studied the GC-MS of plant crude extract in which total 18 compounds were present. In the anti-inflammatory mechanism it was observed that the Ha.Chf inhibits the COX-2 as well as 5-LOX pathways. Results exhibited that this species is a good source of phytocomponents like germacrone, which can be employed as sustainable and a natural therapeutic agent, supporting its traditional use in folk medicine for inflammatory conditions and pain.